MODEL STRATEGI JEJARING KEWIRAUSAHAAN BERKELANJUTAN: KONSEPTUALISASI TEORI KAPASITAS PENYERAPAN DAN TEORI JEJARING SOSIAL - Dwiyana, Annisa; Mahadewi, Lufina (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2025)
This research aims to reveal the essential forms and roles of networking in implementing sustainable entrepreneurship. This research develops a network strategy model of sustainable entrepreneurship to coherently describe how an entrepreneurial network builds sustainable entrepreneurial performance with drivers and enablers in understanding network relationships in the form of formal and informal ties between entrepreneurs and external networks. The novelty of this research was developed and synthesized from the theory of absorptive capacity and social network. The findings of this research signify the form of a networking role model and decision-making by establishing an empirical framework grounded in contextualizing the sustainable entrepreneurial practices. This research provides relevance to the concept of strategic entrepreneurship in network theory, which suggests the strategic orientation of entrepreneurship in network building and externalities that underlie sustainable entrepreneurship implementation practices and entrepreneurial choices in encouraging the growth of sustainable entrepreneurship. Keywords: Social Network, Absorptive Capacity, Sustainable Entrepreneurship, Network Strategy Model of Sustainable Entrepreneurship